Predictors of Disclosure Recipients’ Social Reactions to Victims’ Disclosures of Dating and Sexual Violence: A Longitudinal Study of College Students - Edwards, Katie M. (Journal of interpersonal violence, 2022)
Dating violence (DV) and sexual violence (SV) are pernicious issues among college students that lead to deleterious outcomes, which are more likely when victims receive more negative social reactions (e.g., blaming the victim) and fewer positive social reactions to disclosure (e.g., providing emotional support). Most research studies have examined victims’ reports of social reactions to their assault disclosures, with only a few cross-sectional studies of predictors of disclosure recipients’ provision of positive and negative social reactions to victims. The purpose of the current study was to address these gaps in the literature. Participants were 481 college students (76.4% women, 89.2% White/Non-Hispanic) who reported being a disclosure recipient during the past six months (measured at Time 2 to cross-sectionally and longitudinally predict their social reactions to victims’ disclosures). Results suggested that both victim and disclosure recipient characteristics (e.g., gender, race), disclosure recipient perceptions of victims (e.g., empathy for victim, blame of victim, victims’ coping) and both disclosure recipient and victim behavior at the time of disclosure (e.g., drinking, distress) were related to disclosure recipient social reactions. These findings underscore the need for programs for potential informal disclosure recipients that target psychological variables (e.g., post-traumatic stress disorder) and behavior at the time of disclosure, as well as their perceptions of victims more generally, in addition to improving their knowledge and ability to respond with positive social reactions and avoid negative social reactions.